Pre-season isokinetic screening of neuromuscular risk factors in elite football - Pereira, Rogério (2017)
Abstract Background Neuromuscular isokinetic screening as a pre-season test may identify players at risk of injury or undertrained players. Objective Identify, assess and describe unilateral and bilateral knee muscular deficits in elite football players at pre-season screening. Design Retrospective cohort. Setting Elite football divisions. Patients (or Participants) Of 99 eligible male elite footballers, older than 17 years and without knee injury within the last 6 months, 3 were excluded, resulting in a final sample of 96 players (25 yrs old, BMI 23.7 kg·m−2). Assessment of Risk Factors Knee isokinetic assessment of both limbs was performed, starting with the non-dominant limb. The test range was set and gravity correction was performed. Before each isokinetic test, players were allowed 4 submaximal repetitions. The isokinetic test consisted of concentric sets of 6 and 8 repetitions, at 60˚/s and 180˚/s, respectively. Main Outcome Measurements Peak torque of knee extensors and flexors at 60˚/s and 180˚/s and conventional ratio at 60˚/s and 180˚/s. Individuals were also analysed for bilateral differences (>10%) and conventional ratio – Con/Con – (<0.47 and >0.80). Results Subgrouping by position, bilateral statistically significant differences were more frequent among defenders and goalkeepers, both for knee extensors and flexors (p<0.05). After individual analysis, 19% and 31% of players displayed significant bilateral asymmetries (>10%) for extensor peak torque at 60˚/s and 180˚/s, respectively; while 21% and 44% showed significant bilateral asymmetries for flexor peak torque at 60˚/s and 180˚/s, respectively. The conventional ratio was abnormal among 7% of players, for both dominant and non-dominant limbs at 60˚/s, and among 11% and 9% for dominant and non-dominant limbs, respectively, at 180˚/s. Conclusions Defenders and goalkeepers tended to present bilateral differences for isokinetic parameters more frequently than other player positions. There was a considerable proportion of players with clinically meaningful bilateral asymmetries, also impacting on unilateral balance. This screening is important to tailor neuromuscular programmes addressing deficits believed to be associated with injury risk, relevant in both primary and secondary injury prevention.